Development and characterization of phototrophic aerobic granular sludge - Dahalan, Farrah Aini (2012)
arbon dioxide (CO2) produced in aerobic wastewater treatment has contributed to the greenhouse gases (GHG) emissions in the atmosphere and can cause global warming. Existing biological system of the wastewater treatment needs to be reviewed in order to minimise the emission of GHG especially the CO2. In order to minimise CO2 emission, photosynthetic bacteria can be employed for utilisation of CO2 during the wastewater treatment processes. In this perspective, sequential anaerobic-aerobic process is able to enhance efficient solid-liquid separation through the formation of aerobic granules. The objective of the study looks at the possibility to integrate the three elements: CO2 minimisation, photosynthetic bacteria utilisation and aerobic granulation technology by developing photosynthetic aerobic granular sludge (AGSP) to treat municipal wastewater under phototrophic condition. Synthetic wastewater was used throughout this study to obtain the aerobic granules. Significant physicochemical parameters, i.e. pH, temperature, and light intensity, which enhance phototrophic bacterial growth were determined at the preliminary stage to provide best condition for the growth of photosynthetic bacteria. The optimum physicochemical conditions was applied on a 3-L bioreactor (SBRP) to produce AGSP. After one month of aerobic granules development, mature AGSP gained high settling velocity for efficient settleability of the treated wastewater. The biomass concentration increased from 3 to 14 gL-1. Such growth has resulted a maximum settling velocity of 40 mh-1 with granule average size of ~ 2.0 mm. The high settling velocity was found to be attributed by the smooth, compact, and regular characteristics of the aerobic granules. High magnification microscopic analysis revealed that AGSP was dominated by cocci-shaped bacteria embedded within the extracellular polymeric substances (EPS). Detailed observation on the structure of the AGSP showed the presence of 30 µm of cavity to allow nutrients and gas exchanges within the aerobic granule. Scanning Electron Microscope - Energy-Dispersive X-ray (SEM-EDX) examination showed AGSP composed of different types of inorganic and organic compounds. The presence of high concentration of bacteriochlorophylls (BChl) with 0.86 mg/L in AGSP confirm the presence of photosynthetic pigments in the aerobic granule indicating the occurence of photosynthesis in bacterial cells. AGSP achieved 92% of CO2 reduction and 84% of chemical oxygen demand (COD) removal. The 16s ribonucleic acid (rRNA) sequencing analysis has detected the presence of aerobic, anaerobic and facultative anaerobic bacteria within the granules. The presence of photosynthetic bacteria in the AGSP, i.e Magnetococcus sp, Rhodopseudomonas palustris, Bacteroides thetaiotaomicron, Rhodococcus erythropolis and Desulfovibrio vulgaris showed that CO2 emission in wastewater treatment can be minimised with enhancement of phototrophic conditions.